Tree standing dynamics after 30 years in a secondary forest of Bali, Indonesia - MUSTAID SIREGAR; NI KADEK EROSI UNDAHARTA (Biodiversitas Journal of Biological Diversity, 2018)
Siregar M, Undaharta NKE. 2018. Tree standing dynamics after 30 years in a secondary forest of Bali, Indonesia. Biodiversitas 19: 22-30. Tree standing dynamics in 0.5 ha plot after 30 years in Bukit Tapak secondary forests, Batukahu Nature Reserve, Province 0f Bali was studied by using plot method. The results showed that the tree species richness is same, 33 species, but there are six species disappear and be replaced by another species as a newcomer. Eight species persist as major species based on the importance value, namely: Homalanthus giganteus, Vernonia arborea, Dendrocnide stimulans, Meliosma angustifolia, Saurauia reinwardtiana, Trema orientalis, Macaranga triloba and Polyosma integrifolia. Tree density decreased 19.7%, but the total basal area increased 12.2% with an average basal area per tree were also increased by 39.7%. Shannon diversity index (H`) and Equitability index (E) was increased in 2016. Forests in the plot categorized as old secondary forest are still in the process of maturation toward the primary forest. Species predicted would disappear with a succession of increasingly advanced process is Trema orientalis, while the predicted to survive for much longer are Homalanthus giganteus, Acronichia trifoliolata, Meliosma angustifolia, Polyosma integrifolia, Saurauia reinwardtiana and Dendrocnide stimulans.